2008
DOI: 10.1080/01460860802475176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coping Strategies in Iranian Adolescents with Cancer and Their Parents

Abstract: The diagnosis and treatment of cancer in adolescence requires that adolescents and their parents learn to adjust to the changes associated with cancer. This article presents results about the relationship between parental and adolescent coping. This study examined 120 adolescents in Iran with cancer (aged 11-18) and their parents. Coping was assessed using the Coping Strategies Inventory. Findings showed that there was a positive linear correlation between adolescents' engagement coping and disengagement copin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Research to date provides modest support for the role of parental modeling; however, some associations between parental and child coping have been documented. For example, among families of adolescents with cancer, parents’ and adolescents’ use of engagement coping (e.g., problem solving, cognitive restructuring; Sanjari, Heidari, Hoseini, & Salemi, 2008) and disengagement coping (e.g., problem avoidance; Trask et al, 2003) are concurrently associated. In addition to one-to-one correspondence between parents’ and children’s use of specific coping strategies, there is also evidence of associations across coping strategies, though these associations are not always in the expected direction.…”
Section: Introductionmentioning
confidence: 99%
“…Research to date provides modest support for the role of parental modeling; however, some associations between parental and child coping have been documented. For example, among families of adolescents with cancer, parents’ and adolescents’ use of engagement coping (e.g., problem solving, cognitive restructuring; Sanjari, Heidari, Hoseini, & Salemi, 2008) and disengagement coping (e.g., problem avoidance; Trask et al, 2003) are concurrently associated. In addition to one-to-one correspondence between parents’ and children’s use of specific coping strategies, there is also evidence of associations across coping strategies, though these associations are not always in the expected direction.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing other studies, it was revealed that educated mothers caring for mentally retarded children leads to attitude improvements and better adaptation compared to before training. 21 Sanjari et al, 22 argue that diagnosing and curing cancer require the diseased children and their parents to understand how they should deal with stressful aspects of the disease. Given that parents often take on preparing the daily needs of children, they can use coping procedures to get over the issues.…”
Section: Discussionmentioning
confidence: 99%
“…Esta informação, somada aos indícios de capacidade de manutenção dos recursos familiares evidenciados pelo inventário de Recursos do Ambiente Familiar (RAF), sugere comportamento adaptativo das famílias dos participantes que se encontram em tratamento oncológico. Isso pode influenciar positivamente as estratégias pessoais que serão adotadas pelas crianças e pelos adolescentes em seu processo adaptativo às demandas derivadas do câncer e de seu tratamento (Banner et al, 1996;Sanjari et al, 2008;Walsh, 2005;Wolfe-Christensen et al, 2010). (Castellano-Tejedor, 2015;Gil, 2005;Koocher, 1986;Li et al, 2011;Van Dongen-Melman & Sanders-Woudstra, 1986 (Antoniazzi et al, 1998;Fritz & Williams, 1988;Geist, 1979;Turner-Sack et al, 2012).…”
Section: Inventário De Recursos Do Ambiente Familiar (Raf)unclassified
“…Foi possível elaborar um panorama geral do objeto de estudo, verificando, além dos indicadores de manutenção do funcionamento adaptado das crianças e adolescentes com câncer, a preservação também dos recursos de apoio familiar, em equilíbrio com o grupo de crianças e adolescentes que não foram expostos à situação do adoecimento. As variáveis associadas à rede familiar, neste sentido, configuram-se como um dos principais aspectos que podem favorecer seu processo adaptativo (Banner et al, 1996;Sanjari et al, 2008;Wolfe-Christensen et al, 2010;Walsh, 2005 Essa pesquisa estudará crianças e adolescentes entre 7 e 17 anos, em tratamento contra o câncer, bem como crianças e adolescentes nesta mesma faixa etária, considerados saudáveis. Dessa forma, gostaríamos de convidá-lo a participar dessa pesquisa juntamente com seu(ua) filho(a).…”
Section: Considerações Finaisunclassified